PATTERN OF PRESENTATION AMONG ADULTS HOSPITALIZED WITH DENGUE DISEASE - Rauf, Abdul; Kazmi, Nasir Hussain Shah; Zaman, Haider; Gillani, Saima; Shah, Tariq; Malik, Faizan; Ismaeel, Shoaib (Journal of Ayub Medical College Abbottabad, 2017)
Abstract Background: Dengue is a mosquito born viral infection that has rapidly spread in the world particularly in Southeast Asia. The aim of this hospital based study was to see the demographic, clinical and laboratory characteristics in adults with dengue infection in Hazara region of Northern Pakistan. Method: This is a prospective observational study. Clinical, laboratory and demographic information were collected from adult patients with suspected dengue infection (N= 100) and then managed in one of medical units of tertiary care hospital in Abbottabad from August to October 2015. Results: Total number of patients were 100, 78 were male and 22 were female. 49 patients were in age group from 21 to 40 years. Most patients were from Mansehra district (69), followed by Haripur (11), Abbottabad (11), Batgram (06) and Kohistan (03). Common clinical features were fever (100%), body aches (95%), headache (94%), chills (87%), and anorexia (86%), hemorrhagic tendencies (12%), rash (05%), and sore throat (03%). Thrombocytopenia was observed in 98%, leucopenia in 25%, high Aminotransferases (ALT) in 67%, Ns1 antigen positive 66%, negative 18% and unknown 16%. IgM Antibodies against Dengue Virus was positive 67%, negative 19% and were unknown in 14%, IgG antibodies positive in 54%, negative 32% and were unknown in 14%. Conclusion: We concluded in our study that presentation of dengue infection is same as in other Southeast Asian countries; however, the disease is more prevalent in cities located on plain than hilly areas. Keywords: Dengue, Ades Aegypti, Fever, Pattern, Clinical features, Laborator Characteristics, Hazara Region. Background: Dengue is a mosquito born viral infection that has rapidly spread in the world particularly in Southeast Asia. The aim of this hospital based study was to see the demographic, clinical and laboratory characteristics in adults with dengue infection in Hazara region of Northern Pakistan. Methods: This is a descriptive study. Clinical, laboratory and demographic information were collected from adult patients with suspected dengue infection (n=100) and then managed in one of medical units of tertiary care hospital in Abbottabad from August to October 2015. Results: Total number of patients was 100, 78 were male and 22 were female. 49 patients were in age group from 21 to 40 years. Most patients were from Mansehra district (69), followed by Haripur (11), Abbottabad (11), Battagram (06) and Kohistan (03). Common clinical features were fever (100%), body aches (95%), headache (94%), chills (87%), and anorexia (86%), haemorrhagic tendencies (12%), rash (05%), and sore throat (03%). Thrombocytopenia was observed in 98%, leucopoenia in 25%, high Aminotransferases (ALT) in 67%, Ns1 antigen positive 66%, negative 18% and unknown 16%. IgM Antibodies against Dengue Virus was positive 67%, negative 19% and were unknown in 14%, IgG antibodies positive in 54%, negative 32% and were unknown in 14%. Conclusion: We concluded in our study that presentation of dengue infection is same as in other Southeast Asian countries; however, the disease is more prevalent in cities located on plain than hilly areas. Keywords: Dengue; Ades Aegypti; Fever; Pattern; Clinical features; Laboratory; Characteristics; Hazara Region